In Situ Confocal Raman Microscopy of Hydrated Early Stages of Bacterial Biofilm Formation on Various Surfaces in a Flow Cell. Issue 2 (February 2016) - Smith-Palmer, Truis; Lin, Sicheng; Oguejiofor, Ikenna; Leng, Tianyang; Pustam, Amanda; Yang, Jin; Graham, Lori L.; Wyeth, Russell C.; Bishop, Cory D.; DeMont, M. Edwin; Pink, David
Bacterial biofilms are precursors to biofouling by other microorganisms. Understanding their initiation may allow us to design better ways to inhibit them, and thus to inhibit subsequent biofouling. In this study, the ability of confocal Raman microscopy to follow the initiation of biofouling by a marine bacterium, Pseudoalteromonas sp. NCIMB 2021 (NCIMB 2021), in a flow cell, using optical and confocal Raman microscopy, was investigated. The base of the flow cell comprised a cover glass. The cell was inoculated and the bacteria attached to, and grew on, the cover glass. Bright field images and Raman spectra were collected directly from the hydrated biofilms over several days. Although macroscopically the laser had no effect on the biofilm, within the first 24 h cells migrated away from the position of the laser beam. In the absence of flow, a buildup of extracellular substances occurred at the base of the biofilm. When different coatings were applied to cover glasses before they were assembled into the flow cells, the growth rate, structure, and composition of the resulting biofilm was affected. In particular, the ratio of Resonance Raman peaks from cytochrome c (CC) in the extracellular polymeric substances, to the Raman phenylalanine (Phe) peak from protein in the bacteria, depended on both the nature of the surface and the age of the biofilm. The ratios were highest for 24 h colonies on a hydrophobic surface. Absorption of a surfactant with an ethyleneoxy chain into the hydrophobic coating created a surface similar to that given with a simple PEG coating, where bacteria grew in colonies away from the surface rather than along the surface, and CC:Phe ratios were initially low but increased at least fivefold in the first 48 h.